Paleogene equatorial penguins challenge the proposed relationship between biogeography, diversity, and Cenozoic climate change - Clarke, Julia A. (2007)
New penguin fossils from the Eocene of Peru force a reevaluation of previous hypotheses regarding the causal role of climate change in penguin evolution. Repeatedly it has been proposed that penguins originated in high southern latitudes and arrived at equatorial regions relatively recently (e.g., 4–8 million years ago), well after the onset of latest Eocene/Oligocene global cooling and increases in polar ice volume. By contrast,newdiscoveries from the middle and late Eocene of Peru reveal that penguins invaded low latitudes >30 million years earlier than prior data suggested, during one of the warmest intervals of the Cenozoic. A diverse fauna includes two new species, here reported from two of the best exemplars of Paleogene penguins yet recovered. The most comprehensive phylogenetic analysis of Sphenisciformes to date, combining morphological and molecular data, places the new species outside the extant penguin radiation (crown clade: Spheniscidae) and supports two separate dispersals to equatorial (paleolatitude 14°S) regions during greenhouse earth conditions. One new species, Perudyptes devriesi, is among the deepest divergences within Sphenisciformes. The second, Icadyptes salasi, is the most complete giant (>1.5 m standing height) penguin yet described. Both species provide critical information on early penguin cranial osteology, trends in penguin body size, and the evolution of the penguin flipper.